What users say about international mediators and mediation institutions: Part 2 - ALEXANDER, Nadja (Institutional Knowledge at Singapore Management University, 2020)
In this post on the Kluwer Mediation Blog, the key factors that influence users' choice of mediation institution and choice of the mediator are explored.